Investigating the predictors of intrusive visual imagery in elite athletes - Bierton, J.; Gorman, A.; Lloyd, M.; Gorman, A.; Parker, J. K.; Lovell, G. P. (Journal of Imagery Research in Sport and Physical Activity, 2019)
The aims of this research were to determine if metacognitive beliefs predicted Intrusive Visual Imagery (IVI) in elite athletes, and if this was consistent across performance contexts. To address these aims, 110 elite cricket and AFL players completed the 30-item metacognitions questionnaire and intrusive visual imagery questionnaire before a training session and competitive match. Regression analyses indicated that the Negative Beliefs about the Uncontrollability of Thoughts and Their Danger metacognition and Need to Control Thoughts metacognition predicted IVI in both contexts. Findings were interpreted within the Self-Regulatory Executive Function model. It was suggested that extra attentional control is exerted to prevent the conscious experience of a negative belief, which prompts an image related to the belief being experienced, which is perceived as intrusive. Results also suggested that athletes are less likely to experience IVI before competing, possibly due to greater monitoring of thoughts. Implications for these findings are discussed.